Implications of Quenching‐to‐Dequenching Switch in Quantitative Cell Uptake and Biodistribution of Dye‐Labeled Nanoparticles. Issue 28 (11th May 2021) - Yang, Guangze; Liu, Yun; Hui, Yue; Tengjisi; Chen, Dong; Weitz, David A.; Zhao, Chun‐Xia
Abstract: A general strategy to carry out cell uptake and biodistribution studies is to label nanoparticles (NPs) with a fluorescent dye. However, the comparative study of different dye‐loaded NPs remains difficult owing to uncontrolled dye quenching and de‐quenching. Here we compared two types of dye‐labeled NPs and demonstrated their distinct properties. NPs with dye molecules at a solid state suffer from dye quenching, so the dye release and/or NP degradation in biological environments leads to a several‐fold increase of fluorescence intensity despite the same amount of NPs, owing to the state switch from quenching to de‐quenching. In contrast, NPs with dye molecules at a soluble state exhibit no quenching effect. To standardize the comparative study, we propose two possible solutions: using lower dye loading or using medium analysis for quantifying cell uptake of NPs. This work provides valuable insights into selecting valid quantification methods for bio‐nano studies. Abstract : A ubiquitous quenching‐to‐dequenching switch of dye‐labeled nanoparticles in vitro and in vivo is presented. When dye‐labeled nanoparticles interact with biological systems (cell culture medium, cells, and organs to animals), the dye undergoes the switch, causing a significant increase of fluorescence intensity.